Calculation of Free Bandwidth for Rate-reservation EDF Scheduling in Flash Storage - Lim, Seong-Chae (International Journal of Computer Sciences and Engineering, 2020)
In the long history of database communities, lots of research efforts had been done for reducing seek-times and rotational delays caused by mechanical components used in HDD (Hard Disk Drive). As an example of those efforts, some I/O scheduling algorithms were devised for the purpose of efficient services of online video streams being pumped up from HDD storage. To this end, a rate-reservation EDF is recently adopted to be incorporated into the recent platform built on flash storage. In this research, a fixed length of time is chosen as a period unit and the disk bandwidth assumption of each video stream is decided based on that time. The previous rate-reservation EDF algorithm is very suitable for serving a mixture of real-time requests and common requests without deadline. In this paper, we propose a new way that can dynamically compute the varying amounts of free bandwidth arising from more-than-reservation reading, while scheduling video streams according to the rate-reservation EDF algorithm. For this, we devised two data structures that can keep information about workloads and free bandwidth over a certain length of period units. Using scheduling information managed in those data structures, our proposed scheme can efficiently utilize slack times that occur unexpectedly from time to time. Because of the efficient reclamation of slack times, our scheme can improve the actual I/O performance of flash storage that is prepared for Web-based streaming services.